MICROBIAL ENZYMATIC REDUCTION OF IRON NANOPARTICLES FOR THE CONTROL OF HUMAN PATHOGENS, STAPHYLOCOCCUS AUREUS, AND SALMONELLA TYPHI - C, MUNUSAMY; K, CHANDHIRASEKAR; M, PREMKUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of this study was to synthesis, characterize, and evaluation of antimicrobial potential of iron nanoparticles (Fe NPs) using Serratia marcescens. Methods: Fe NPs were fabricated by microbial enzyme using ferric chloride as an agent of reduction and stabilization. Fe NPs formation and their elemental nature were confirmed by ultraviolet (UV)-absorption spectroscopy and energy dispersive X-ray spectroscopy, respectively. The morphology of Fe NPs was characterized by a scanning electron microscope (SEM). Functional groups of biomolecules associated with Fe NPs were inferred from characteristic Fourier transform infrared (FTIR) spectroscopy peaks. The antibacterial activity is determined by the disc diffusion method. Results: Synthesized Fe NPs exhibited characteristic UV-absorption spectrum peaks at 263nm. FTIR spectroscopy peaks of Fe NPs, 3411.66, 1629.16, 1039.63, and 601.90 cm−1 corresponds to carbonyl, disulfides, and ethers groups. SEM study demonstrated that the average size was from 200nm with interparticle distances. The crystalline nature of Fe NPs was confirmed from the X-ray diffraction peaks analysis. The intense diffraction peaks due to Fe NPs at 16.32, 22.56, 35.54, 41.08, 52.36, 61.42, 66.42, 78.1, and 85.08. Corresponding to the 110, 150, 200, 430, 550, and 950 facets of the face-centered cubic crystal structure conformed to the Joint Committee on Powder Diffraction Standards: 89-3722 of iron. Antimicrobial activity of Fe NPs against tested Gram-positive and negative bacterial strains showed significant inhibitory zones. Conclusion: The inhibitory zones obtained in the present study reveal that the Fe NPs can act as a good antibacterial agent.